A New Type of External Fixation - Jasińska-Choromańska, D.; Deszczyński, J. (Engineering Transactions, 2003)
The paper presents some problems related to external osteosynthesis. Design of the new generation of external fixators should use modelling, computer simulation and clinical postulates. New generation of external fixators has been equipped with the measuring system of the bone healing process. Some of the important problems connected with the mechatronical and clinical aspects of the external fixator design and clinical application are presented.